Physiological and pharmacologic aspects of peripheral nerve blocks - Prasanna Vadhanan; Debendra Kumar Tripaty; S Adinarayanan (Wolters Kluwer Medknow Publications, 2015)
A successful peripheral nerve block not only involves a proper technique, but also a thorough knowledge and understanding of the physiology of nerve conduction and pharmacology of local anesthetics (LAs). This article focuses on what happens after the block. Pharmacodynamics of LAs, underlying mechanisms of clinically observable phenomena such as differential blockade, tachyphylaxis, C fiber resistance, tonic and phasic blockade and effect of volume and concentration of LAs. Judicious use of additives along with LAs in peripheral nerve blocks can prolong analgesia. An entirely new group of drugs-neurotoxins has shown potential as local anesthetics. Various methods are available now to prolong the duration of peripheral nerve blocks.